Measurement and immunophenotyping of pleural fluid EpCAM-positive cells and clusters for the management of non-small cell lung cancer patients. (January 2019) - Thompson, Jeffrey C.; Fan, Ryan; Black, Taylor; Yu, Gordon H.; Savitch, Samantha L.; Chien, Austin; Yee, Stephanie S.; Sen, Moen; Hwang, Wei-Ting; Katz, Sharyn I.; Feldman, Michael; Vachani, Anil; et al.
Highlights: First study to evaluate PEC enumeration and immunophenotyping in pleural fluid. Detection of PECs in pleural effusions may be utilized to diagnose a MPE. CellSearch® enables the non-invasive immunophenotyping of PECs from MPEs. First study to demonstrate the prognostic value of the enumeration of PECs in MPEs. Abstract: Objectives: A malignant pleural effusion (MPE) is a common complication in non-small cell lung cancer (NSCLC) with important staging and prognostic information. Patients with MPEs are often candidates for advanced therapies, however, the current gold standard, cytological analysis of pleural fluid samples, has limited sensitivity. We aimed to demonstrate the feasibility of non-invasive enumeration and immunophenotyping of EpCAM-positive cells in pleural fluid samples for the diagnosis of a MPE in NSCLC patients. Materials and methods: Pleural fluid specimens were prospectively collected from patients with NSCLC and the CellSearch® technology was utilized for the enumeration of pleural EpCAM-positive cells (PECs) and determination of PD-L1 expression on PECs from pleural fluid samples. The diagnostic performance of the enumeration of single PECs and PEC clusters was assessed using receiver operating characteristic (ROC) curves. The Kaplan-Meier method and Cox proportional hazards model was used to assess the impact of PECs and PEC clusters on overall survival (OS). Results: 101 NSCLC patients were enrolled. The median number of PECs was significantly greater in the malignant (n = 84) versus non-malignant group (n = 17) (730 PECs/mL vs 1.0 PEC/mL, p < 0.001). The area under the ROC curve was 0.91. A cutoff value of 105 PECs/mL had a sensitivity and specificity of 73% and 100% for the diagnosis of a MPE, respectively. Among 69 patients with a pathology-confirmed MPE and tissue immunohistochemistry (IHC) results, 15 (22%) had greater than 50% PD-L1+ PECs. Overall concordance between tissue and PEC PD-L1 expression was 76%. Higher numbers of pleural effusion single PECs were associated with inferior overall survival (Cox adjusted HR 1.8, 95% CI: 1.02–3.05 p = 0.043). Conclusion: Non-invasive measurement of PECs in NSCLC patients, using an automated, clinically available approach, may improve the diagnostic accuracy of a MPE, allow for immunophenotyping of PECs, and provide prognostic information.